Energy saving by integrated control of natural ventilation and HVAC systems using model guide for comparison - Homod R.Z.; Sahari K.S.M.; Almurib H.A.F. (Elsevier Ltd, 2023)
Integrated control by controlling both natural ventilation and HVAC systems based on human thermal comfort requirement can result in significant energy savings. The concept of this paper differs from conventional methods of energy saving in HVAC systems by integrating the control of both these HVAC systems and the available natural ventilation that is based on the temperature difference between the indoor and the outdoor air. This difference affects the rate of change of indoor air enthalpy or indoor air potential energy storage. However, this is not efficient enough as there are other factors affecting the rate of change of indoor air enthalpy that should be considered to achieve maximum energy saving. One way of improvement can be through the use of model guide for comparison (MGFC) that uses physical-empirical hybrid modelling to predict the rate of change of indoor air potential energy storage considering building fabric and its fixture. Three methods (normal, conventional and proposed) are tested on an identical residential building model using predicted mean vote (PMV) sensor as a criterion test for thermal comfort standard. The results indicate that the proposed method achieved significant energy savings compared with the other methods while still achieving thermal comfort. © 2014 Elsevier Ltd.